COVID‐19 and hematology findings based on the current evidences: A puzzle with many missing pieces - Karimi Shahri, Mehdi (Int J Lab Hematol, 2020)
In December 2019, a new type of coronavirus was detected for the first time in Wuhan, Hubei Province, China. According to the reported data, the emerging coronavirus has spread worldwide, infecting more than fifty‐seven million individuals, leading to more than one million deaths. The current study aimed to review and discuss the hematological findings of COVID‐19. Laboratory changes and hematologic abnormalities have been reported repeatedly in COVID‐19 patients. WBC count and peripheral blood lymphocytes are normal or slightly reduced while these indicators may change with the progression of the disease. In addition, several studies demonstrated that decreased hemoglobin levels in COVID‐19 patients were associated with the severity of the disease. Moreover, thrombocytopenia, which is reported in 5%‐40% of patients, is known to be associated with poor prognosis of the disease. COVID‐19 can present with various hematologic manifestations. In this regard, accurate evaluation of laboratory indicators at the beginning and during COVID‐19 can help physicians to adjust appropriate treatment and provide special and prompt care for those in need.